European Union initiatives in child immunization-the need for child centricity, e-health and holistic delivery - Rigby,MJ; Chronaki,CE; Deshpande,SS; Altorjai,P; Brenner,M; Blair,ME (European Journal of Public Health, 2020)
BACKGROUND: Low childhood immunization rates in Europe are causing concern and have triggered several EU initiatives. However, these are counter-factual as they make immunization a stand-alone issue and cut across best practice in integrated child health services. They also focus unduly on 'anti-vax' pressures, generalize 'vaccine hesitancy' and overlook practical difficulties and uncertainties encountered by parents in real world situations about presenting children for immunization. Meanwhile European expertize in child health electronic record systems and relevant standards are ignored despite their being a potentially sound foundation ripe for enhancement. METHODS: Situation and literature reviews, and cohesion of two European research projects, led to shared investigation. As a result, two cross-sectoral expert workshops were held to consider digital health standards for harmonizing integrated preventive child health including immunization, and the work of other stakeholders such as the World Health Organisation and the European Centre for Disease Control. RESULTS: Progress in child health information models and digital health standards was assessed, areas needing further standards development identified and desirable steps towards innovation in service delivery and record keeping agreed. CONCLUSION: The European Commission, member states and child health stakeholders should take an integrated approach to child health with immunization as a component. Service delivery should be sensitive to parental concerns and challenges, and the way child- and family-centric data are recorded and used should be enhanced. Services should be enabled by the International Patient Summary and related electronic health record standards and linkages, and evaluated to assess most effective systems and practice.